Psychosocial factors in the military environment and their influence within the family. (2018)
The military context has different dynamics that provide spaces for reflection and interest, in this sense, the research was proposed, whose purpose was to analyze the psychosocial factors in the military environment of the soldiers of the General Manuel Valdivieso de Facatativá and their influence on the performance of their roles in the family. Through a qualitative approach and the methodological process of the authors Bonilla and Rodríguez. In relation to the results, there are intrapersonal, interpersonal, intra-employment and extra-occupational factors, causing them to pass through their daily lives generating various feelings and actions, it is also highlighted that the role occupied by the military in the labor field permeates their family dynamics.